PENINGKATAN LITERASI KEUANGAN SYARIAH DI DESA SENDANG MELALUI DIGITALISASI: PELUANG DAN TANTANGAN DI ERA MODERN - Muhammad Adi Adrian; Agus Suaidi Hasan; Zumrotun Nazia; Anna Putri Syafitri; Niswatin Mubarriroh (PT. Jurnal Center Indonesia Publisher, 2026)
Sharia financial literacy has become important with the development of digital financial services and the increasing need for financial management in accordance with sharia principles. However, the understanding of rural communities regarding digital-based sharia finance is still limited. This community service activity aims to improve Islamic financial literacy in Sendang Village through a digital approach. The methods used include face-to-face and online education, assistance in using Islamic financial applications, and interactive discussions on the opportunities and risks of digital finance. The results of the activity showed that community participation reached 75% with an increase in understanding of Islamic finance products and principles of 60%. However, challenges such as the digital divide and the risk of online fraud were still found. Overall, this activity shows that digitalization is effective in increasing Islamic financial literacy when supported by continuous education and the active role of the government and Islamic financial institutions in creating a safe and inclusive ecosystem.